Thinking politically about social work in child protection and welfare: A radical Reappropriation of the works of Hannah Arendt - Susan Flynn (Child Protection and Practice)
This article presents a theoretical exposition of Arendtian political philosophy for child protection and welfare social work. The aim is to better understand and inform social work in the field of child protection and welfare, whilst accounting for the political context of practice. Sustaining the exposition is the view that power-laden child protection systems are ultimately socio-political through their authority to intervene in private family life. This is partly owing to the instrumental power inherent in child protection systems to exert dominance and control over service users and social groups leading to raced, gendered and classed outcomes in child welfare. To unpack the political nature of social work in child protection and welfare, a tripartite conceptual frame of private, public and social domains is derived from Arendt’s philosophical work. This is critically applied to put forward seven propositions for how social work can develop in child protection and welfare, with respect to practice in a socio-political context. Practical implications for future social work include implementing evidence-informed advocacy efforts and conducting empirical research toward preserving balance in social work attention to public and private life.